Organizational Communication Climate in the Organizational Culture of Public Services (The Department of Investment and Integrated Services of One Door Pringsewu Regency, Lampung) - Sone, Rennia (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2020)
A good organizational communication climate requires an in-depth study of each organization. The organization of communication climate plays a role in encouraging members of the organization to devote employees’ efforts to their work in organizations where the change of organization system can also have a positive influence on the organizational communication climate. The organizational communication climate is part of an organizational culture that includes values, traditions, norms, which are bound by trust, intimacy, and responsibility. This study aims to understand and express the organizational communication climate in the culture of government public service organizations. This study uses descriptive qualitative method. The research subjects are employees in the Department Of Investment and Integrated Services of One Door Pringsewu Regency. Data collection techniques used in this study are observation, structured interviews, and documentation. Data analysis is conducted by selecting relevant data, exposing it, and drawing conclusions. This study concludes that the existing organizational culture is closely related to the organizational communication climate and the leadership's attitude in managing work, colleagues, which improves service quality.